Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres